Analisis Peran Petugas Aviation Security Dalam Pemeriksaan Barang Bawaan Penumpang Yang Membahayakan Keamanan Penerbangan Di Screening Check Point 2 Bandar Udara Abdulrahman Saleh Malang - Mochammad Rilo Pambud; Rosiana Ulfa (Jurnal Mahasiswa Kreatif, 2023)
Along with the development of science and technology that is very fast and increasingly widespread, the need for comfortable, safe and fast transportation facilities is very much needed by transportation users, especially in the use of air transportation, in ensuring the safety of flights at airports is an obligation for all personnel. Aviation security, especially those on duty at the Screening check-point to carry out their duties correctly and consistently according to the instructions contained in the applicable regulations. Airport security officers play an important role in terms of security for passengers providing the best service in order to meet passenger expectations or satisfaction, the purpose of this study is to find out what the role is and to find out what the obstacles and solutions are from the aviation security unit in handling passenger luggage that endangers flight securit. This study used qualitative research methods. Data collection techniques in this study were interviews, observation, and documentation. The techniques used in this study were data reduction, data presentation and conclusions/verification. Through sources, namely Mr Wawan senior Avsec, Mrs Galuh senior Avsec and Mrs Citra junior Avsec. From the results of the research that the author has done, Aviation Security plays an important role in ensuring security for users of aviation transportation services, and in carrying out their duties in accordance with the applicable Standard Operation Procedures (SOP), and always coordinating with related parties, then for the constraints face, namely from limitations in terms of the availability and quality of the technology used for inspection of passenger luggage. Although there are a variety of detection equipment, sometimes the technology may not be sophisticated enough or capable of accurately detecting objects that are a real flight hazard. Then in handling the problem the airport must improve the limited technology availability system for checking passenger luggage, sometimes the technology may not be sophisticated enough or unable to accurately detect objects that are indeed dangerous to flights